(untitled) (Journal of Interior Design and Academy, 2023)
Furniture that does not conform to ergonomic measurements causes feelings of fatigue, attention disorders and some health problems. Due to the fact that this situation affects perceptual performance, efficiency and academic achievement, it is considered important to determine ergonomics studies for furniture design in educational buildings. In this context, it is aimed to analyze the studies conducted by literature review method. The scanning carried out using the concepts of ergonomics, furniture, student is limited to a table and a chair. It has been found that furniture that does not physically adapt to students leads to disorders in body posture and health problems such as lower back, neck, back pain, as well as psychological problems such as lack of concentration. In this case, it has been concluded that there should be a strong relationship between furniture dimensions and anthropometric measurements of students.